The Impact of Green Accounting and Corporate Social Responsibility on the Profitability of LQ-45 Firms - Komara, Edi; Bangun, Putri Metha Ulinka (SAN Scientific, 2025)
This study analyzes the influence of green accounting (environmental costs and environmental performance) and corporate social responsibility (CSR) on the profitability (ROA) of LQ-45 Firms listed on the Indonesia Stock Exchange (IDX) from 2019-2022. Using purposive sampling, eight Firms were selected. Data was obtained from annual financial and sustainability reports. Environmental costs were measured using the Environmental Cost Index, environmental performance with the PROPER rating, and CSR disclosure using GRI91 criteria. Profitability was measured by ROA. Multiple linear regression analysis in SPSS 25 showed that: (1) Environmental costs did not significantly affect ROA. (2) Environmental performance had a positive significant effect on ROA. (3) CSR disclosure had a negative significant effect on ROA. (4) Simultaneously, environmental costs, environmental performance, and CSR disclosure influenced ROA. Managerial implications highlight the importance of strong environmental performance in increasing profitability. Management must carefully plan CSR programs to balance social benefits and costs. Investors should assess Firms' environmental and social management as part of investment decisions. Regulators should enforce policies promoting transparency in CSR disclosure and green accounting practices to enhance corporate accountability and sustainability.